The Impact of Atmospheric Dry Deposition Associated Microbes on the Southeastern Mediterranean Sea Surface Water following an Intense Dust Storm - Rahav, Eyal; Paytan, Adina; Chien, Chia-Te; Ovadia, Galit; Katz, Timor; Herut, Barak (Frontiers in Marine Science, 2016)
This study explores the potential impacts of microbes deposited into the surface seawater of the southeastern Mediterranean Sea (SEMS) along with atmospheric particles on marine autotrophic and heterotrophic production. We compared in situ changes in autotrophic and heterotrophic microbial abundance and production rates before and during an intense dust storm event in early September 2015. Additionally, we measured the activity of microbes associated with atmospheric dry deposition (also referred to as airborne microbes) in sterile SEMS water using the same particles collected during the dust storm. A high diversity of prokaryotes and a low diversity of autotrophic eukaryotic algae were delivered to surface SEMS waters by the storm. Autotrophic airborne microbial abundance and activity were low, contributing 1% of natural abundance in SEMS water and accounting for 1-4% to primary production. Airborne heterotrophic bacteria comprised 30-50% of the cells and accounted for 13-42% of bacterial production. Our results demonstrate that atmospheric dry deposition may supply not only chemical constitutes but also microbes that can affect ambient microbial populations and their activity in the surface ocean. Airborne microbes may play a greater role in ocean biogeochemistry in the future in light of the expected enhancement of dust storm durations and frequencies due to climate change and desertification processes.